Design and Build System for Web Employee Performance Assessment at PT. Bahtera Noah Indonesia - Ishak Alexander; Sharyanto; Bernadus Gunawan Sudarsono (Yayasan Bina Internusa Mabarindo, 2022)
PT.Bahtera Noah Indonesia, which is desired by the company for workers, has a quality standard to measure work success. However, because the company is newly established and does not yet have an employee performance appraisal system, a web-based employee performance appraisal information system is needed. The stages of system development in making this information system use the Prototyping model method which consists of the planning stage, the analysis stage, the design stage, and the implementation stage. Using the PHP programming language in making and MySQL Server as the database. The result of the research is that the system that was running previously did not have storage in the form of a database, so that the data storage process became more difficult to search, so it was proposed to improve the current employee performance appraisal system. With the performance appraisal system at PT. Bahtera Noah Indonesia makes employee performance appraisals computerized.